Odpowiedzi

Najlepsza Odpowiedź!
2009-12-12T13:11:15+01:00
2.
d) 2-(3a-7)/4+(a+17)/5=0 |*20
40-5*(3a-7)+4*(a+17)=0
40-15a+35+4a+68=0
143-11a=0 |-143
-11a=-143 |:(-11)
a=13
e) (b+6)/2+(5-4b)/3=(8-b)/6 |*6
3*(b+6)+2*(5-4b)=8-b
3b+18+10-8b=8-b
-5b+28=8-b |+5b-8
20=4b |:4
b=5
f) (9c+7-2c)/2+(c-2)/7=36 |*14
7*(9c+7-2c)+2(c-2)=504
63c+49-14c+2c-4=504
51c+45=504 |-45
51c=459 |:51
c=9
3.
a) 1+(x+2)²/2=x²-½(x+1)² |*2
2+x²+4+4x=2x²-x²-1-2x
6+4x+x²=x²-1-2x |-x²+2x
6+6x=-1 |-6
6x=-7 |:6
x=-1⅙
b) (x-3)²-(x-7)/2=7-(x+1)(1-x) |*2
2x²+18-12x-x+7=14-2+2x² |-2x²
25-13x=12 |-25
-13x=-13 |:(-13)
x=1
c) (y-1)²-(y+4)/3-4=(y-4)(4+y) |*3
3y²+3-6y-y-4-12=-48+3y² |-3y²
-13-7y=-48 |+13
-7y=-35 |:(-7)
y=5
d) (3y-2)²/4-(y+1)²=1,25(y-1)(y+1)-0,5² |*4
9y²+4-12y-4y²-4+8y=5*(y²-1)-0,25*4
5y²-4y=5y²-5-1 |-5y²
-4y=-6 |:(-4)
y=1,5
2 3 2